(untitled) (Bangladesh Journal of Medical Science, 2025)
Ethical judgments differ according to personal characteristics. Our study aimed to determine the relationship between ethical positions (idealism and relativism subdimensions) and psychological well-being. The study’s second aim was to compare socio-demographic characteristics, taking medical ethics courses, participating voluntarily in social responsibility projects and religiosity with ethical positions and psychological well-being. The Ethical Positions Questionnaire and Flourishing Scale have been used to collect the data. The research sample comprises first- to sixth-grade medical students (n=246) in Turkey. The study found a significant relationship between idealism ethics position and psychological well-being. A significant relationship was also found between engaging in prosocial behaviours and psychological wellbeing. In addition, among the participants, those who defined themselves as religious had high idealism and well-being scores, and those who did not define themselves as religious had high relativism scores. Further research is needed to identify more features that affect ethical judgments. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 164-176